Speed skating - Brimner, Larry Dane (New York Children's Press, 1997)
A brief overview of the sport of speed skating including its history, equipment, categories of events, and memorable performances by speed skaters at the Olympic games
Includes bibliographical references (p. 44) and index
Hurg
5
Keywords: Ice skating; Speed skating